Aortoiliac Occlusion Disease - Rossi, Umberto G.; Ierardi, Anna M.; Cariati, Maurizio (AORTA, 2022)
Leriche syndrome is characterized by abdominal aorta and/or bilateral iliac occlusive disease, with a triad of clinical symptoms and signs such as claudication, erectile dysfunction, and decreased distal pulses. Diagnostic imaging is one of the key factors for diagnosis of the anatomic origin of the Leriche symptoms. We report the case of a 56-year-old man with diagnosis of abdominal aorta and bilateral iliac occlusive disease with a wide collateral vascular network.
Keywords: aorta; iliac; artery; occlusion; vascular disease; imaging